Early hemodynamic and renal effects of hemorrhagic shock resuscitation with lactated Ringer's solution, hydroxyethyl starch, and hypertonic saline with or without 6% dextran-70 - Nascimento, Paulo; de Paiva Filho, Odilar; de Carvalho, Lidia Raquel; Braz, José Reinaldo Cerqueira [UNESP] (Elsevier B.V., 2006)
Background. Considering the renal effects of fluid resuscitation in hemorrhaged patients, the choice of fluid has been a source of controversy. In a model of hemorrhagic shock, we studied the early hemodynamic and renal effects of fluid resuscitation with lactated Ringer's (LR), 6% hydroxyethyl starch (HES), and 7.5% hypertonic saline (HS) with or without 6% dextran-70 (HSD).Materials and methods. Forty-eight dogs were anesthetized and submitted to splenectomy. An estimated 40% blood volume was removed to maintain mean arterial pressure (MAP) at 40 mm Hg for 30 min. The dogs were divided into four groups: LR, in a 3:1 ratio to removed blood volume; HS, 6 mL kg(-1); HSD, 6 mL kg(-1); and HES in a 1:1 ratio to removed blood volume. Hemodynamics and renal function were studied during shock and 5, 60, and 120 min after fluid replacement.Results. Shock treatment increased MAP similarly in all groups. At 5 min, cardiac filling pressures and cardiac performance indexes were higher for LR and HES but, after 120 min, there were no differences among groups. Renal blood flow and glomerular filtration rate (GFR) were higher in LR at 60 min but GFR returned to baseline values in all groups at 120 min. Diuresis was higher for LR at 5 min and for LR and HES at 60 min. There were no differences among groups in renal variables 120 min after treatment.Conclusions. Despite the immediate differences in hemodynamic responses, the low-volume resuscitation fluids, HS and HSD, are equally effective to LR and HES in restoring renal performance 120 min after hemorrhagic shock treatment. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: hemorrhagic shock; renal function; crystalloid; colloid; hypertonic saline; dog